The Influence of Light Exposure in Ambiance during Pregnancy inMaternal and Fetal Outcomes: An Experimental Study - Vitor Coca Sarri; Beatriz Maria Ferrari; Larissa Fernandes Magalhães; Paula Almeida Rodrigues; Almir Coelho Rezende; Marisa Afonso Andrade Brunherotti (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective The aim of this study is to evaluate whether exposure to different environmental lighting conditions affects the reproductive parameters of pregnant mice and the development of their offspring. Methods Fifteen pregnant albino mice were divided into three groups: light/dark, light, and dark. The animalswere euthanized on day 18 of pregnancy following the Brazilian Good Practice Guide for Euthanasia of Animals.Maternal and fetal specimens weremeasured and collected for histological evaluation. Analysis of variance (ANOVA) test was used for comparison of the groups considering p ≤ 0.05 to be statistically significant. Results There was no significant difference in the maternal variables between the three groups. Regarding fetal variables, significant differences were observed in the anthropometric measures between the groups exposed to different environmental lighting conditions, with the highest mean values in the light group. The histological evaluation showed the same structural pattern of the placenta in all groups, which was within the normal range. However, evaluation of the uterus revealed a discrete to moderate number of endometrial glands in the light/dark and light groups, which were poorly developed in most animals. In the fetuses, pulmonary analysis revealed morphological features consistent with the transition from the canalicular to the saccular phase in all groups. Conclusion Exposure to different environmental lighting conditions had no influence on the reproductive parameters of female mice, while the offspring of mothers exposed to light for 24 hours exhibited better morphometric features.